The Importance of Exercise in Maintaining Human Health - Zarofat Igamberdievna Yuldasheva (Euro Asian Journal Publishing, 2023)
Human health is a very fragile system that requires constant monitoring and support. But how to properly take care of it? Will only proper nutrition and strengthening the immune system help with this? How to choose optimal physical activity, and are they necessary at all? Similar questions often arise among sedentary people. Speaking about the benefits of physical activity, it should be noted that their intensity, frequency, and work on the muscles and skeleton are important. The lifestyle of a modern person is sedentary, since most professions involve sedentary work. As a result, the body does not experience the constant necessary load and becomes less and less dexterous and mobile, and the vital activity of all organs and systems becomes more and more sluggish
Keywords: physical culture; physical education; physical activity; program and regulatory documents on physical education